Awake craniotomy for supratentorial gliomas: why, when and how?. (September 2012) - Ibrahim, George M; Bernstein, Mark
SUMMARY Awake craniotomy has become an increasingly utilized procedure in the treatment of supratentorial intra-axial tumors. The popularity of this procedure is partially attributable to improvements in intraoperative technology and anesthetic techniques. The application of awake craniotomy to the field of neuro-oncology has decreased iatrogenic postoperative neurological deficits, allowed for safe maximal tumor resection and improved healthcare resource stewardship by permitting early patient discharge. In this article, we review recent evidence for the utility of awake craniotomy in the resection of gliomas and describe the senior author's experience in performing this procedure. Furthermore, we explore innovative applications of awake craniotomy to outpatient tumor resections and the conduct of neurosurgery in resource-poor settings. We conclude that awake craniotomy is an effective and versatile neurosurgical procedure with expanding applications in neuro-oncology.